(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the semantic characteristics and structural composition of German proverbs, emphasizing their role as a reflection of cultural identity and linguistic creativity. The research explores the figurative meanings, metaphorical frameworks, and grammatical patterns within German proverbs. Through semantic analysis and comparative linguistic approaches, the study identifies the underlying conceptual metaphors and syntactic structures that contribute to the expressiveness and universality of German proverbs. Furthermore, the paper highlights the cognitive, cultural, and communicative functions of proverbs in the German linguistic system.